Determinan Status Pemanfaatan Jaminan Kesehatan pada Pekerja Informal di Provinsi Lampung Tahun 2020 - Nadiesa Syahla Ramadhani; Tiodora Hadumaon Siagian (Politeknik Statistika STIS, 2022)
The government has prepared a health insurance program as an effort to improve the health status of the community. The percentage of utilization of health insurance in Lampung Province is the lowest nationally. This shows that the government's efforts in preparing the Health Insurance Program have not been fully utilized by the people of Lampung. Considering that informal workers are vulnerable to risk of accidents, this study aims to obtain variables that significantly affect the status of health insurance utilization for informal workers in Lampung Province in 2020. The data used is Susenas Kor in 2020. The research method used is binary logistic regression. The results showed that the variables of age and regional typology had a significant effect on the status of health insurance utilization. Older informal workers (≥ 46 years) and informal workers who live in urban areas have a higher tendency to take advantage of their health insurance.